Insert x + 3 instead of x into the equation of the function f(x):
f(x) = 3 - 6x²
f(x + 3) = 3 - 6(x + 3)²
use (a + b)² = a² + 2ab + b²
= 3 - 6(x² + 2(x)(3) + 3²) = 3 - 6(x² + 6x + 9)
use distributive property
= 3 + (-6)(x²) + (-6)(6x) + (-6)(9) = 3 - 6x² - 36x - 54
combine like terms
= -6x² - 36x - 51
<h3>Answer: f(x + 3) = -6x² - 36x - 51</h3>
2x-x=-13+5
x=-8
I think so
Good luck
Answer:
4
Step-by-step explanation:
because, if y = 4 and x = 1 then it would be 4/1 or 4 just simplify.
Y/X --- Y = 4 --- X = 1 ---- that makes 4/1 or 4
Answer:
x=0
Step-by-step explanation:
Subtract 1 from both sides
2x+1-1<1-1
Simplify the arithmetic
2x<1-1
Simplify the arithmetic
2x<0
Isolate the X
X=0